2003
DOI: 10.1021/cm0208004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polarized Photoluminescent Films Derived from Sequential Self-organization, Induced-Orientation, and Order-Transfer Processes

Abstract: Mechanical shearing of N,N‘-bis(N,N-diethylaminoethyl)perylene-3,4:9,10-bis(dicarboximide) dihydrochloride in a lyotropic liquid-crystalline phase produced oriented solid films that exhibit highly anisotropic fluorescence emission. The highest emission intensity is observed when the shearing direction of the film is perpendicular to the polarization axes of the excitation and emission light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…8,15 In contrast, scanning tunneling microscopic (STM) studies of C n -PTCDI derivatives deposited on MoS 2 and HOPG substrates demonstrated a preferential alignment of perylene domains with respect to the underlying substrate lattice. 14 In addition, the molecular orientation of surface-adsorbed perylene derivatives is influenced by varying degrees with appropriate choice of substituent, 37,38 application of mechanical shear force, 39,40 and by post-deposition annealing in the presence of water 35 or solvent 5 vapor. By making no a priori assumptions regarding substrate interactions or molecular structure, the current study emphasizes that both post-deposition processing, i.e., annealing, and choice of substrate can substantially affect the orientation of adsorbed perylene.…”
Section: Resultsmentioning
confidence: 99%
“…8,15 In contrast, scanning tunneling microscopic (STM) studies of C n -PTCDI derivatives deposited on MoS 2 and HOPG substrates demonstrated a preferential alignment of perylene domains with respect to the underlying substrate lattice. 14 In addition, the molecular orientation of surface-adsorbed perylene derivatives is influenced by varying degrees with appropriate choice of substituent, 37,38 application of mechanical shear force, 39,40 and by post-deposition annealing in the presence of water 35 or solvent 5 vapor. By making no a priori assumptions regarding substrate interactions or molecular structure, the current study emphasizes that both post-deposition processing, i.e., annealing, and choice of substrate can substantially affect the orientation of adsorbed perylene.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 In addition to polarized absorption of light, these films also showed polarized fluorescent emission. 59 The axis perpendicular to the shearing direction of the film exhibits higher emission intensity than the axis parallel to the shearing direction. The ratio of the emission intensities along the orthogonal directions was as high as 30 at 690 nm, the wavelength of maximum emission intensity.…”
Section: Fabrication Of Oriented Filmsmentioning
confidence: 97%
“…55 Shear-induced alignment is another important technique for aligning chromonic nematic liquid crystals. 31,32,35,37,[56][57][58][59] Shear-induced orientation and reorientation of the cyanine dye 9 and C.I. Acid Red 266 (10) were examined by Tiddy and co-workers.…”
Section: Fabrication Of Oriented Filmsmentioning
confidence: 99%
“…Achieving alignment thus opens a wide variety of opportunities for the production of functional chiral materials for application in organic semiconductors, thinfi lm polarizers, thin-fi lm transistors, lasers, and solar cells via controlled self-organization of bent-core molecules. [10][11][12][13][14] Currently available evidence indicates that it is diffi cult to achieve macroscopically oriented domains of the B4 phase. The B4 grows from the higher temperature fl uid smectic or isotropic phase via a fi rst-order phase transition in which nanofi lament formation starts at dilute nucleation sites.…”
Section: Doi: 101002/adma201004482mentioning
confidence: 99%